Physiochemical Analysis of Cocoa Powder-Like from Roasted Seeds of Fermented Nephelium lappaceum L. (Rambutan) and Nephelium mutabile Bl. (Pulasan) Fruits - Hazrulrizawati, Hamid; Aizi Nor Mazila, Ramli; Izzah Hayati, Yahaya (Malaysian Institute of Chemistry, 2021)
The present study demonstrated the physiochemical analysis of cocoa powder-like from roasted seeds of fermented rambutan and pulasan fruits in comparison to commercial cocoa powder. The crude fat content of cocoa powder (25.70%) was lower compared to both rambutan and pulasan seeds (35.00%). The major fatty acids in pulasan seed were similar to cocoa fat, which were stearic acid and petroselinic acid. The major cocoa-like flavour components, pyrazine was found in both rambutan and pulasan seeds. Lower saponin content was obtained in pulasan seed compared to rambutan seed. Meanwhile, pulasan seed contained higher TPC concentration than rambutan seed. Both fruit seeds were concluded to have high potential to be utilized as cocoa powder substitute in the future and this could open up a new direction in the flavour and fragrance sector, and in the s manufacture of cocoa-like food products